Optimization of Hollow Fiber Liquid-Phase Microextraction Combined with GC-ECD for Determination of Organochlorine Pesticides in Orange Juice - Demirci*, Ayla; Gevrek, Emel (Asian Journal of Chemistry, 2014)
The hollow fiber protected liquid phase microextraction (HF-LPME) technique was evaluated for the extraction of organochlorine pesticides in orange juice prior to gas chromatography-electron capture detection (GC-ECD) analysis. At first, the effects of the HF-LPME experimental parameters on the enrichment factor were studied simultaneously using a 25–1 fractional factorial design. The HF-LPME variables of interest were extraction time, stirring speed, acceptor phase, salt (NaCl, w/v %) and pH. In the next step, a two-level plus centre point fractional factorial experiment was performed to evaluate the effects of three parameters, including the extraction time, stirring speed and pH of donor phase. The optimized HF-LPME conditions were as follows: an extraction time of 20 min, a stirring speed of 800 rpm, an acceptor phase of toluene, no salt and a source pH of 6. The extraction calibration plots were linear over the range of 0.25-10 ng mL–1 (r2: 0.9863-0.9995) and the limits of detection for ten pesticides studied were from 0.012 to 0.456 ng mL–1. Good enrichment factors were achieved (66-251-fold) with this method and good repeatabilities were obtained, with relative standard deviations below 19.9 %.